Implementasi Algoritma Learning Vector Quantization Dalam Aplikasi Pengenalan Pola - Rumetna, Matheus Supriyanto; Ninia Lina, Tirsa; Karay, Jeni; Budi Santoso, Agustinus; Greogory Kaitelapatay, Big; Komansilan, Reinhard (PETIR, 2023)
Along with the development of technology, a lot of technology has emerged and aims to make computers intelligent so that they can mimic the daily work of humans. One of the jobs that is often done is typing documents from a book or article. If the typed document is not too long, it will not cause problems. However, if there are quite a lot of documents to be typed, the operator will need a relatively long time to complete the job. This work can be streamlined by utilizing Artificial Intelligence, namely the Learning Vector Quantization (LVQ) algorithm. LVQ is used because it can learn, calculate distances and separate clusters from the patterns it has learned. This application is implemented using the Microsoft Visual Basic 6 programming language. The result is that the application can segment image characters, and carry out the training process as well as the process of recognizing patterns or shapes of characters, which in turn can recognize each character in a sentence. As well as displaying the steps in the training process and the recognition process, so that it can help learning the LVQ algorithm, especially in character recognition.